The verb in archaic Biblical poetry: a discursive, typological, and historical investigation of the tense system - Notarius, Tania (Studies in Semitic languages and linguistics, 2013)
Preliminary Material -- Preliminary Notes -- 1 Verbal Tenses in Classical Biblical Prose: A Selected Bibliographical review -- 2 The Problem of Verbal Tenses in Biblical Poetry: Review of Research -- 3 Verbal Tenses in Poetry: The Methodological Standpoint -- 4 The Song of Moses (Deut 32:1–43) -- 5 The Song of the Sea (Exod 15:1–18) -- 6 The Song of Deborah (Jdg 5:2–30) -- 7 The Song of David (II Sam 22:2–51) -- 8 The Blessing of Jacob (Gen 49:2–27) -- 9 The Oracles of Balaam (Num 23:7–10, 18–24; 24:3–9, 15–19) -- 10 The Blessing of Moses (Deut 33:2–29) -- 11 The Song of Hannah (I Sam 2:1–10) -- 12 The Historical Linguistic Study of the Archaic Hebrew Verb: Methodological Observations -- 13 The Archaic Phenomena of Verbal Morphosyntax -- 14 The Archaic Hebrew Verb and Signs of Linguistic Diversity -- Bibliography -- Indexes.